Setting Time and Compressive Strength of Geopolymers Made of Three Indonesian Low Calcium Fly Ash with Variation of Sodium Silicate Addition - Ririn Eva Hidayati; Fitria Sandi Faradilla; Dadang Dadang; Lia Harmelia; Nurlina Nurlina; Didik Prasetyoko; Hamzah Fansuri (Archives of Metallurgy and Materials, 2021)
In this research, the effect of sodium silicate (Na2SiO3) on the geopolymerization of fly ash type F (low calcium) has been studied. The variations of Na2SiO3 used in the synthesized geopolymers were 19, 32, and 41wt%. The fly ash from three different power plant sources was characterized using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), Particle Size Analyzer (PSA), and Scanning Electron Microscopy (SEM). Fly ash-based geopolymers were tested for mechanical strength and setting time. The best geopolymer was obtained by adding 32% Na2SiO3, produced a compressive strength of 21.62 MPa with a setting time of 30 hours. Additions of 19wt% Na2SiO3 failed to form geopolymer paste while the addition of 41wt% Na2SiO3 decreased the mechanical strength of the geopolymer. Higher calcium content in low calcium fly ash produces stronger geopolymer and faster setting time.